Influence of weather conditions of crop on harvest quality and post-harvest behavior of pineapple guava fruit - Parra-Coronado, Alfonso (2019)
The weather conditions of crop, which define the properties or attributes of the feijoa fruits at the time of harvest, also determine the behavior of the same during post-harvest. In this study, the effect of the weather conditions of the crop on some fruit quality attributes at the harvest, as well as on its behavior during the post-harvest period, was evaluated. Two farms were considered located in different localities of the department of Cundinamarca - Colombia, located at altitudes of 1,800 masl and 2,580 masl, in each of which 20 trees were marked and the weather conditions registered during the development period of the fruits until the harvest, for two different periods of production. The parameters of quality in the period of development of the fruits until the harvest, as well as during the post-harvest period, were evaluated periodically. In postharvest, fruits differentiated by location were stored at temperatures of 5 ± 1oC (87 ± 5% RH) and 18 ± 1oC (76 ± 5% RH), with assessment of quality parameters every 2 days. The conclusion of the study was that the quality fruit in the harvest and during the post-harvest depends on the weather conditions of crop. Fruits produced at higher altitudes have higher content of total soluble solids, larger size and weight, presenting in post-harvest less weight loss and less firmness and acidity. At higher storage temperature, the fruits presented more weight loss and firmness, higher sugar content and less durability.